Solvatochromic, Photophysical and DFT Studies of Newer 1-(2- oxo-2-(2-oxo-2H-chromen-3-yl)ethyl)pyridin-1-ium Bromide and 1-methyl-3-(2-oxo-2-(2-oxo-2H-chromen-3-yl)ethyl)-1H-imidazol- 3-ium Bromide Synthesized under Microwave Irradiation - Patil, Atul S.; Patil, Raosaheb S.; Patil, Vikas S.; Mahulikar, Pramod P. (Current Physical Chemistry, 2022)
Background: Pyridinium and imidazolium-based compounds show diverse applications with basic skeleton designs in order to achieve improved optical and thermal behavior. Aim: The aim of the study was to design and develop a greener, efficient protocol towards newer pyridinium and imidazolium compounds, and investigate optical, solvatochromic, thermal, and theoretical properties. Objectives: The purpose is to study the optical properties of pyridinium and imidazolium compounds, for which we illustrate the solvent polarity effect on the absorption and emission behavior as a function of orientation polarizability and ET(30) solvent parameters. The study focuses on thermal stability and computes the molecular orbital orientation and HOMO- LUMO energies using theoretical simulation by the DFT approach. Methods: The structures were confirmed by FT-IR, Mass, 1H NMR and 13C NMR, and optical properties were investigated using a UV-Visible spectrophotometer and fluorometer. The thermal behavior was investigated using thermal gravimetric analysis, and molecular orbital orientation and energies were determined using GAUSSIAN 16 software. Results: The newer compounds with good thermal stability and optical behavior have been synthesized and characterized. The study interprets the intermolecular electron transfer amongst the molecules and the effect of solvents on their excitation and emission properties. The experimental and theoretical study illustrates the optical, thermal, and electronic properties of both compounds. Conclusion: The present work describes the solvatochromic optical behavior of pyridinium bromide and imidazolium bromide synthesized by a microwave-assisted, greener and efficient strategy. The solvatochromic study interprets the presence of non-specific solutesolvent interactions. The photophysical, thermal, and DFT study revealed that both pyridinium and imidazolium compounds are used for optoelectronic applications. Moreover, the work could be helpful to researchers for developing new skeletons for optoelectronic applications.
Keywords: Microwave-assisted synthesis